Role of hormone replacement therapy in treatment of women with chronic renal failure – potential benefits and hazards - Kos-Kudła, Beata; Marek, Bogdan; Kajdaniuk, Dariusz; Staszewicz, Paweł; Ostrowska, Zofia (Menopause Review/Przegląd Menopauzalny, 2002)
Patients with chronic renal failure (CRF) show an excess mortality from cardiovascular disease. In patients with CRF there have been identified many risk factors for cardiovascular diseases including estrogen deficiency which can manifest in women with CRF as premature menopause and it is associated with high risk not only for cardiovascular complications but for renal osteodystrophy as well. It is now well established that hormone replacement therapy (HRT) has beneficial effects on various atherosclerotic parameters in population of postmenopausal women and its role in primary prevention of coronary artery disease has been reported in many studies. There is still a question of debate if advanteges of HRT reported in studies based on general population of postmenopausal women can also be observed in women with CRF and estrogen deficiency.